2009
DOI: 10.1016/j.engstruct.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic dynamic traffic load effects in bridges

Abstract: When formulating an approach to assess bridge traffic loading with allowance for Vehicle-Bridge Interaction (VBI), a trade-off is necessary between the limited accuracy and computational demands of numerical models and the limited time periods for which experimental data is available. Numerical modelling can simulate sufficient numbers of loading scenarios to determine characteristic total load effects, including an allowance for VBI. However, simulating VBI for years of traffic is computationally expensive, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…Thus, bridge codes recommend higher dynamic allowances for shorter spans. Nevertheless, a number of authors have shown that the sitespecific dynamic amplification derived from VBI simulation models and field data can represent a significant reduction with respect to these recommendations and save an existing bridge from unnecessary rehabilitation or demolition (Gonzalez et al, 2008a;OBrien et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, bridge codes recommend higher dynamic allowances for shorter spans. Nevertheless, a number of authors have shown that the sitespecific dynamic amplification derived from VBI simulation models and field data can represent a significant reduction with respect to these recommendations and save an existing bridge from unnecessary rehabilitation or demolition (Gonzalez et al, 2008a;OBrien et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, it can be seen that the 3 rd , 4 th and 5 th largest static strains exceed the 3 rd , 4 th and 5 th largest total strains. It should also be noted that there is a general trend of decreasing dynamics with increasing static load and this is expected [15,16].…”
Section: Daf and Adrmentioning
confidence: 99%
“…OBrien et al [15,16] suggest that DAF does not recognize the reduced probability of both maxima occurring simultaneously, i.e., static load effect and dynamic amplification. They point out that the maximum values of DAF tend to result from lighter vehicles and are not relevant when seeking characteristic maximum values and propose the concept of Assessment Dynamic Ratio (ADR).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Brady et al [94] observed that the amplification of frequency response due to a single passing vehicle is considerably more than for two vehicles simultaneously passing in opposite directions, thereby indicating the influence of vehicle direction. In a subsequent study, O'Brien et al [95] allocated the cause of this phenomenon to single vehicle crossing behaviour mirroring a bridge's first mode shape pattern, thus amplifying the dynamic response. Other, more complex bridge traffic crossing events, where vehicle locations and velocities are such that they induce dynamic amplification, are much less probable.…”
Section: Problematic Effects Of Environmental and Operational Conditionsmentioning
confidence: 99%